(untitled) (Fiep Bulletin - online, 2024)
Introduction: It is foreseen in the Constitution of the Federative Republic of Brazil, in the Universal Declaration of Human Rights, that it is the duty of the state to promote the conditions for the population to have access to health and quality of life. Objective: To analyze how the effects of physical education and physical exercise contribute to ensuring the quality of life of those who exercise. Methods: This is a field research, with a quantitative approach, which is initially related to the analysis of the laws and norms that regulate physical education in Brazil, in the search to understand the way in which physical exercise promotes the quality of life of bodybuilders and how it is provided for in Brazilian legislation. To assess quality of life, the SF-6D questionnaire was used. 30 physical exercisers participated. Results: The quality of life of the 30 (thirty) participants was distributed as follows: 03 (three) individuals inserted in the house 0.85 to 0.86; 17 (seventeen) individuals represented in the range of 0.9 to 0.95; 10 (ten) individuals included in the range of 0.95 to 1 on the standard gamble scale. It appears that the closer the result is to 1, the better the quality of life of the person evaluated. Conclusion: it was proven that those who practice physical exercise achieved an indicator of quality of life very close to the maximum level of the scale used by the SF-6D questionnaire, a fact that corroborates the assertion that physical exercise promotes an improvement in quality of life.